A comparative study of state self-esteem responses to social media feedback loops in adolescents and adults - Chen, Yu-Hsing (Frontiers in Psychology, 2025)
IntroductionSocial media platforms provide constant, quantifiable feedback that can shape self-esteem, particularly during adolescence, a period of heightened neurobiological sensitivity to social evaluation. While previous research has examined digital feedback effects on well-being, comparative evidence on adolescents and adults remains limited. This study investigated how feedback valence, social comparison, and perceived authenticity influence state self-esteem across these developmental groups.MethodsA cross-sectional, quasi-experimental design was employed with 240 urban Chinese participants (120 adolescents aged 13–18 years and 120 adults aged 25–40 years). Participants were randomly assigned to positive, neutral, or negative feedback conditions within a simulated social media environment. State self-esteem was assessed using the State Self-Esteem Scale, with social comparison orientation and perceived authenticity measured as potential mediating and moderating factors. Data were analyzed using ANOVA, mediation, and moderation models with covariate controls.ResultsAdolescents demonstrated significantly greater sensitivity to feedback than adults, with larger increases in self-esteem after positive feedback and sharper decreases after negative feedback (Age × Valence interaction, F(2,234) = 6.65, p = 0.002). Main effects of feedback valence were observed across both groups (F(2,237) = 10.85, p < 0.001). Mediation analyses indicated that social comparison orientation partially accounted for the relationship between feedback valence and self-esteem, while moderation analyses revealed that perceived authenticity buffered against the negative effects of unfavorable feedback. All five preregistered hypotheses were supported.DiscussionFindings highlight adolescence as a developmental stage of heightened vulnerability to digital evaluation, reflecting neurocognitive imbalance between socio-affective reactivity and regulatory control. Social comparison emerged as a mechanism that amplifies feedback effects, whereas authenticity functioned as a protective factor across all ages. These results refine theoretical models of digital self-esteem regulation and suggest targeted interventions for adolescents, including digital literacy curricula, resilience-building, and platform design modifications to mitigate comparison pressures.